Presencia y significación de la muerte en la obra de Gustavo Adolfo Bécquer - Meza Alegría, Gabriel; Montes Brunet, Hugo (Acta Hispanica, 2016)
In this paper we trace the presence of death in the works of Gustavo Adolfo Bécquer, identify the way it is manifested through his Rimas and propose a classification of the types of death present in his legends. This is carried out with the aim of understanding the textualization of death in the becquerian works and determine the connections with aspects such as Romanticisms, mystic and spirituality. We propose that death is an essential element in the poetics of the author, which reveals a transcendentalist vision that crosses the main creative aspects of the Spanish poet.